CONSTANŢA CRISTESCU: CONTRIBUTIONS TO THE VALORIFICATION OF THE MUSICAL TRADITION OF BANAT AND TRANSYLVANIA, MUSICAL PUBLISHING HOUSE, BUCHAREST, 2011 - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica)
The year 2011 was very rich and creative for the musicologist Constanta Cristescu. Three volumes of musicology creations were published under her signature. Among them, the work presented here is called “Contributions to the Capitalisation of the Musical Tradition from Banat and Transylvania” edited by the Editura Muzicala from Bucharest. The contents are divided into two large chapters: I. Historiography, Rhetoric and Stylistics and II. Ethnomusicology. Chapter I has six studies; four of them deal with different aspects of the Romanian music of a Byzantine tradition. They are as follows: 1. The Rhetoric and the Stylistics of the Romanian Music of a Byzantine Tradition; 2. Stylistic Features of the Romanian Singing with a Byzantine Tradition of Ardeal; 3.Tradition and Innovation in the Liturgical Music of a Byzantine Tradition; 4. The Oral in the Hymnography of a Byzantine Tradition. The other two studies of the first chapter present, using two novel manuscripts, two important personalities of the church teachers and singers of Arad from the end of the 19th century and the first part of the 20th century, Valeriu Magdu and Atanasie Lipovan.